Oral infections in oral cancer survivors: A mini-review - Pispero, Alberto; Lombardi, Niccolò; Manfredi, Maddalena; Varoni, Elena Maria; Sardella, Andrea; Lodi, Giovanni (Frontiers in Oral Health, 2022)
The oral cancer survivors are a group of special individuals whose disease affect anatomical structures with a key role in identity and communication and a fundamental role in basic human functions such as speaking, eating, swallowing and breathing. Thus, quality of life of these individuals can be impaired by the consequences of disease and treatments, in particular surgery and radiotherapy. Among others, infectious conditions of any nature, bacterial, viral, fungal, are a frequent finding among oral cancer survivors. In fact, the peculiar systemic and local conditions of these subjects are known to significantly modify the microbiota, which, besides facilitating opportunistic infections, can affect the cancer microenvironment, as well as alter the effects of the anti-cancer therapies. Similarly, mouth infections can also affect the prognosis of oral cancer survivors. Among the opportunistic infections, fungal are the most common infections affecting these subjects, since neutropenia resulting from cancer, as well as chemotherapy and/or radiotherapy treatments, promote the shift from the carrier state of Candida species, to pathogen state. Treatment of oral candidiasis can be difficult in oral cancer survivors, and good evidence supports clotrimazole as the most effective for prevention, and fluconazole as the one with the best risk-benefit profile. Probiotics, although promising, need better evidence to be considered an effective treatment or preventive measure.